A panel travel cost model accounting for endogenous stratification and truncation: A latent class approach - Hynes, S.; Greene, William (University of Wisconsin Press, 2013)
In this paper, we develop a panel data negative binomial count model that corrects for endogenous stratification and truncation. We also incorporate a latent class structure into our panel specification, which assumes that the observations are drawn from a finite number of segments, where the distributions differ in the intercept and the coefficients of the explanatory variables. The paper argues that count data panel models corrected for on-site sampling may still be inadequate and potentially misleading if the population of interest is heterogeneous with respect to the impact of the chosen explanatory variables. © 2013 by the Board of Regents of the University of Wisconsin System.